A structural equation model of factors associated with HIV risk behaviors and mental health among men who have sex with men in Malawi - Yuan Zhao; Amrita Rao; Andrea L. Wirtz; Eric Umar; Gift Trapence; Vincent Jumbe; Sosthenes Ketende; Dunker Kamba; Chris Beyrer; Stefan Baral (BMC Infectious Diseases, 2020)
Abstract Background Men who have sex with men (MSM) bear a disproportionate burden of HIV in Malawi. Early prevention efforts in Malawi have been largely focused on preventing heterosexual and vertical transmission of HIV, and MSM have rarely been the specific benefactors of these efforts, despite facing both higher prevalence of HIV coupled with multiple barriers to prevention and care. To better facilitate the design of culturally relevant HIV prevention programs and prioritize resources among MSM in resource limited settings, the objective of this analysis was to estimate the relationship between social factors and HIV related risk behaviors and mental health. Methods 338 MSM were recruited using respondent-driven sampling in Blantyre, Malawi from April 2011 to March 2012. Structural equation models were built to test the association between six latent factors: participation in social activities, social support, stigma and human rights violations, depression symptomatology, condom use, and sexual risk behaviors, including concurrent sexual partnerships and total number of partners. Results The mean age of participants was 25 years old. Almost 50% (158/338) of the participants were unemployed and 11% (37/338) were married or cohabiting with women. More than 30% (120/338) of the participants reported sexual behavior stigma and 30% (102/338) reported depression symptomatology. Almost 50% (153/338) of the participants reported any kind of HIV-related risk behaviors and 30% (110/338) participated in one of the recorded social activities. Significant associations were identified between stigma and risk behaviors (β = 0.14, p = 0.03); stigma and depression symptomatology (β = 0.62, p = 0.01); participation in social activities and depression symptomatology (β = 0.17, p = 0.01). Conclusion Results suggest MSM reporting stigma are more likely to report sexual risk practices associated with HIV/STI transmission and depressive symptoms, while those reporting participation in social activities related to HIV education are less likely to be depressed. Furthermore, interventions at the community level to support group empowerment and engagement may further reduce risks of HIV transmission and improve mental health outcomes. Taken together, these results suggest the potential additive benefits of mental health services integrated within comprehensive HIV prevention packages to optimize both HIV-related outcomes and general quality of life among MSM in Malawi.